The Redistributive Effects of Financial Deregulation - Korinek, Anton (IMF Working Papers; Working Paper ;, 2013)
Financial regulation is often framed as a question of economic efficiency. This paper, by contrast, puts the distributive implications of financial regulation center stage. We develop a model in which the financial sector benefits from risk-taking by earning greater expected returns. However, risktaking also increases the incidence of large losses that lead to credit crunches and impose negative externalities on the real economy. We describe a Pareto frontier along which different levels of risktaking map into different levels of welfare for the two parties. A regulator has to trade off efficiency in the financial sector, which is aided by deregulation, against efficiency in the real economy, which is aided by tighter regulation and a more stable supply of credit. We also show that financial innovation, asymmetric compensation schemes, concentration in the banking system, and bailout expectations enable or encourage greater risk-taking and allocate greater surplus to the financial sector at the expense of the rest of the economy.